Uma perspectiva macroecológica sobre o risco de extinção em mamíferos - Reis, Vinícius Silva (2019)
The dynamics of diversity on the planet lead to the appearance and disappearance of species over time. The fossil record currently forms a consistent body of evidence about extinction events and this phenomenon raises a fundamental question in the study of biodiversity: Why do some species become extinct and disappear from systems and others not? In this thesis I took a macroecological approach to achieve the overall goal of elucidating global causes for mammalian extinction risk. In the first chapter, I partitioned the relative importance of phylogenetic age, body size and the change of the geographical distribution of species in determining the risk of global mammal extinction. I accounted for the uncertainty in estimating predictors in both current and extinct species. I showed that body size is the single best predictor of extinction risk in mammals, followed by the combined effect of body size and phylogenetic age. Both the insertion of extinct species and the consideration of the uncertainty in predictors were important in extinction risk analysis. In the second chapter, I examined whether landmass size have influenced mammalian extinction risk by restricting the change in the size of geographic distribution and/or limiting dispersal in search of suitable habitats for survival. I found that continental physical limits globally influence the extinction risk of mammals. Continental boundaries prevent mammalian species from following environments suitable for survival in a context of climate change. I further showed that this limitation functions as a horizontal spatial constraint for mammalian dispersal. Thus, mammals that are more limited by landmass size are more likely to become extinct over time in the course of climate change. In the third chapter, I assessed whether this same restrictive effect of landmasses on the ability of species to follow suitable environments for survival influenced the extinction of the Megafauna at the end of the Quaternary. In this context, I also compared two methods of analysis of the obtained data, the generalized least squares and the quantile regression. I concluded that the extinction that wiped out much of Megafauna was a complex, nonlinear event. Megafauna has been limited on its ability to disperse to new regions where the climate would allow it to survive longer. This limitation was imposed by the edge of the continents, causing smaller landmasses to lose more species of megafauna.